Development of head protector for judo practice considering neck extension suppression - Kamitani, T.; Onidani, N.; Omiya, M.; Konosu, A. (Journal of Biomechanical Science and Engineering, 2017)
Severe head injuries—and even deaths—have been reported in the practice of judo, often resulting from inexperience in using the appropriate falling technique (ukemi). In this study, we developed a novel head protector that protects the head and suppresses the neck extension during impact with the mat. The head protector was fabricated for this purpose and consists of a head support structure and shock-absorbing materials. The effectiveness of the head protector was tested experimentally with an apparatus with head and neck components that were based on a Hybrid III dummy. Several configurations of the support structure characteristics and the shock-absorbing materials were evaluated. The proposed head protector was capable of reducing the head angular velocity variation range—which is an important evaluation index for the onset of acute subdural hematoma —by 29% using the devices alone, by 21% using shock-absorbing materials alone, and by 47% using a combination of both. These results show that the proposed structures are highly effective in suppressing extensions at the cervical-thoracic joint (C7-T1), whereas the shock-absorbing materials are highly effective in suppressing rotations at the atlanto-occipital joint (O-C1). It is concluded that wearing the proposed head protector—which combines both effects—can reduce the risk of severe head injuries, even those resulting from severe impacts such as those associated with the judo ukemi practice.